2018
DOI: 10.1016/j.envres.2017.11.044
|View full text |Cite
|
Sign up to set email alerts
|

The deepwater horizon oil spill coast guard cohort study: A cross-sectional study of acute respiratory health symptoms

Abstract: Results from the present study suggested strong relationships between oil and oil dispersant exposures and acute respiratory symptoms among disaster responders. Future prospective studies will be needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Research on past oil spills has shown some acute health consequences among clean-up workers and individuals from affected communities, including anxiety and post-traumatic stress [ 7 ], eye and skin irritation [ 8 ], and lower respiratory tract symptoms [ 9 ] up to one year following oil spill exposure. In several studies, longer durations of oil spill work were associated with acute respiratory symptoms, including among US Coast Guard personnel deployed to work on the Deepwater Horizon spill [ 10 ], and Hebei Spirit oil spill workers [ 11 ]. Persistent respiratory symptoms were observed among clean-up workers 5 years following the Prestige oil spill [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on past oil spills has shown some acute health consequences among clean-up workers and individuals from affected communities, including anxiety and post-traumatic stress [ 7 ], eye and skin irritation [ 8 ], and lower respiratory tract symptoms [ 9 ] up to one year following oil spill exposure. In several studies, longer durations of oil spill work were associated with acute respiratory symptoms, including among US Coast Guard personnel deployed to work on the Deepwater Horizon spill [ 10 ], and Hebei Spirit oil spill workers [ 11 ]. Persistent respiratory symptoms were observed among clean-up workers 5 years following the Prestige oil spill [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While oil spills have occurred across the world, studies on the associated mid- and long-term health effects have been reported only in three countries: Spain (Prestige oil spill), the USA (Exxon Valdez oil spill [ 19 , 20 , 21 ] and the BPDH oil spill [ 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]), and Korea (HSOS) [ 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. There have been concerns pertaining to the potential development of cancers in the affected areas; however, few studies have focused on the cancer incidence among residents after the oil spill despite their consequent exposure to carcinogenic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our study cannot rule out the possibility of an early inflammatory response with subsequent downregulation. Part of the previous work on the respiratory system effects of VOCs inhalation from oil spills focused on acute effects (Alexander et al 2018;Campbell et al 1993;Janjua et al 2006;Lyons et al 1999;Morita et al 1999), yet there is a significant knowledge gap on the inflammatory response associated with such outcomes. Such studies have reported symptom descriptions, with few collecting spirometric data, blood hematology and biochemistry, or exposure analytes in urine, and did not attempt to gain insights on the biological mechanisms of the acute respiratory response through assessments of respiratory tract inflammation.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…Studies on oil VOC exposure by cleaning personnel reported a variety of acute and short-term effects, including manifestations consistent with upper airway and whole respiratory tract irritation. Such data were collected from the Deepwater Horizon leak (Alexander et al 2018;Goldstein et al 2011) and other spills (Campbell et al 1993(Campbell et al , 1994Janjua et al 2006;Lyons et al 1999;Meo et al 2008Meo et al , 2009Morita et al 1999). Asthma attacks were also reported (Eggleston 2007;Goldstein et al 2011;Leikauf 2002;Nurmatov et al 2013).…”
Section: Introductionmentioning
confidence: 99%